Time to tracheostomy impacts overall outcomes in patients with cervical spinal cord injury. Issue 2 (August 2020) - Anand, Tanya; Hanna, Kamil; Kulvatunyou, Narong; Zeeshan, Muhammad; Ditillo, Michael; Castanon, Lourdes; Tang, Andrew; Gries, Lynn; Joseph, Bellal
Abstract : BACKGROUND: The morbidity associated with cervical spine injury increases in the setting of concomitant cervical spinal cord injury (CSCI). A significant proportion of these patients require placement of a tracheostomy. However, it remains unclear if timing to tracheostomy following traumatic CSCI can impact outcomes. The aim of our study was to characterize outcomes associated with tracheostomy timing following traumatic CSCI. METHODS: We performed a 5-year (2010–2014) analysis of the American College of Surgeons Trauma Quality Improvement Program database and included all adult (age, ≥18 years) trauma patients who had traumatic CSCI and received tracheostomy. Patients were subdivided into two groups: early tracheostomy (ET) (⩽4 days from initial intubation) and late tracheostomy (LT) (>4 days). Outcome measures included respiratory complications, ventilator-free days, intensive care unit–free days and hospital length of stay, and mortality. Multivariate logistic regression analysis was performed. RESULTS: A total of 5, 980 patients were included in the study, of which 1, 010 (17%) patients received ET, while 4, 970 (83%) patients received LT. Mean age was 46 years, and 73% were men. In terms of CSCI location, 48% of the patients had high CSCI (C1–C4), while 52% had low CSCI (C5–C7). Patients in the ET group had lower rates of respiratory complications (30% vs. 46%, p = 0.01), higher ventilator-free days (13 days vs. 9 days; p = 0.02), intensive care unit–free days (11 days vs. 8 days; p = 0.01), and a shorter hospital length of stay (22 days vs. 29 days; p = 0.01) compared with those in the LT group. On regression analysis, ET was associated with lower rates of respiratory complications in patients with high CSCI (odds ratio, 0.55 [0.41–0.81]) and low CSCI (odds ratio, 0.93 [0.72–0.95]). However, no association was found between time to tracheostomy and in-hospital mortality. CONCLUSION: Early tracheostomy regardless of CSCI level may lead to improved outcomes. Quality improvement efforts should focus on defining the optimal time to tracheostomy and considering ET as a component of SCI management bundle. LEVEL OF EVIDENCE: Therapeutic, level IV. Abstract : Supplemental digital content is available in the text.